Election fourty five: Reflections on the revolution in Britain - Austin Mitchell; MITCHELL (Austin) (London Fabian Society, 1995)
''The story of the 1945 election is told by those who took part: Fabians, candidates and elected MPs of the three main parties...Britain has had three revolutions, the Civil War, the Glorious Revolution and 1945. The first two changed the elite and the regime. The 1945 election did that in a massive transfusion of new blood but also ushered in a new social, political and economic settlement. A radical programme was carried through by a government of giant figures who built a welfare state, and an economy run for full employment and high and sustainable growth on Keynesian lines with its commanding heights in public ownership. That settlement endured until Margaret Thatcher's counter revolution."--BOOK JACKET.
Keywords: Elections; Great Britain; Road to Revolution